2000
DOI: 10.1021/bm000011k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfated Colominic Acids and Their Interaction with Fibroblast Growth Factors

Abstract: Colominic acid, an alpha (2-->8)-linked poly(sialic acid), was sulfated and characterized by NMR spectroscopy. During sulfation, the secondary hydroxyl group at C-4 had almost the same reactivity as the primary hydroxyl group at C-9, while the secondary hydroxyl group at C-7 was hardly substituted. Analysis by molecular modeling suggested that the lack of substitution at C-7 was due to a steric hindrance. A mobility shift assay indicated that FGF-2 bound to the sulfated colominic acid. Synthetic sulfated colom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
(83 reference statements)
0
25
0
Order By: Relevance
“…( Scheme 5 ). 49 As this method is not selective as to the location or number of sulfates incorporated on the sugar hydroxyl groups, and the molecules had been completely characterized after their initial synthesis, further NMR and mass spectral analysis was not conducted. Instead, elemental analysis for % sulfur (%S) was completed.…”
Section: Resultsmentioning
confidence: 99%
“…( Scheme 5 ). 49 As this method is not selective as to the location or number of sulfates incorporated on the sugar hydroxyl groups, and the molecules had been completely characterized after their initial synthesis, further NMR and mass spectral analysis was not conducted. Instead, elemental analysis for % sulfur (%S) was completed.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it has been reported that NCAM can associate with a receptor for members of signaling glial cell line-derived neutrophic factor (40). Synthetic sulfated polysialic acid binds to abasic FGF and basic FGF as strongly as heparin (41). It is thus possible that polysialic acid of NCAM on myotubes concentrates FGF and presents it to FGF receptors, thus providing a signal to stop further myoblast fusion.…”
Section: Discussionmentioning
confidence: 87%
“…The proliferation of aortic endothelial cells strongly depends on the activity of endogenous fibroblast growth factor-2 (FGF-2) (Schweigerer et al, 1987;Sato and Rifkin, 1988). Although SCA binds FGF-2 and potentiates the mitogenic activity of fibroblastic 3T3-L1 cells, CA does not potentiate the FGF-2 activity (Kunou et al, 2000). It is possible that CA serves as a scavenger of endogenous FGF-2; as a result, the stimulation of endothelial cell proliferation by the growth factor is reduced.…”
Section: Discussionmentioning
confidence: 99%